Research Trends in Higher-Order Thinking Skills in the journal Mathematics Education in Indonesia: from Design to Data Analysis - Kania, Nia; Kusumah, Yaya S.; Dahlan, Jarnawi Afgani; Nurlaelah, Elah; Arifin, Zaenal (EDUPEDIA Publisher, 2024)
The study identified research trends in higher-order thinking skills in Mathematics Education in Indonesia, from Design to Data Analysis. The data came from content analysis of math education articles. As of April 2022, mathematics education articles in the Science and Technology Index (SINTA) are used solely. The Indonesian Ministry of Research, Technology, and Higher Education founded SINTA (http://sinta2.ristekdikti.go.id) to evaluate science and technology. This research shows that qualitative methods, such as theme analysis or grounded theory, can provide insight into student learning, while quantitative methods, such as regression or multivariate analysis, provide statistical analysis of HOTS factors. Recommendations include improving teaching, research, and policymaking on choosing the correct analysis method and institutional support. Diversification and data analysis are essential to improve HOTS research and support Indonesian education development.